Awareness About RNTCP And Dots Guidelines Among Health Care Professionals of a Tertiary Care Hospital of South India - Pragati V Chavan; Debjyoti Datta; Rajashri S Patil; Arun Daniel J (Medsci Publications, 2014)
Background:Nursing and house surgeons' roles in the WHO DOTS (directly observed therapy short course) strategy cover the entire spectrum of activities, including advocating for political commitment, case detection, administering and monitoring drug regimens, ensuring a regular supply of medicines, and standardizing recording and reporting systems. In view of this, their knowledge regarding TB disease, RNTCP, and the current guidelines of WHO DOTS strategy, was assessed. Materials & methods: A cross sectional study was conducted among 82 nurses and 25 house-surgeons between May to July 2012 in a tertiary care hospital of South India. A pre tested structured questionnaire was used to assess their awareness on TB disease, RNTCP and DOTS guidelines. Awareness was assessed using scores and analysed by mean, proportions and Chi square test, using Microsoft Excel 2010. Results: The knowledge about TB, RNTCP and new DOTS guidelines was 28.0%, 63.4% and 19.5% respectively among nurses and 84%, 60% and 40% respectively among house-surgeons. Conclusion: The level of awareness regarding TB and RNTCP guidelines amongst the house-surgeons and nurses was satisfactory but the knowledge regarding the new DOTS guidelines was inadequate.